TRAUMATIC EXPERIENCES OF LAURA IN DANNY AND MICHAEL PHILIPPOU’S BRING HER BACK (2025) - Nova Rahmadini, Indria; Hikmatullah, Affan; Divia, Fachri Ilham; Nurini, Nunik; Rakes, Putri Zaskia (Linguistics and Literature Journal, 2025)
This study analyzes Laura’s traumatic experiences in Danny and Michael Philippou’s Bring Her Back (2025) using Herman’s trauma typology and Caruth’s psychoanalytic theory of belatedness.  The research aims to explain how Laura’s psychological instability, fragmented memories, and sensory distortions reflect different forms of trauma while illustrating the psychoanalytic dynamics of repetition and delayed understanding.  Employing a qualitative descriptive method, the analysis focuses on scenes depicting intrusive flashbacks, dissociation, hypervigilance, and emotional breakdowns.  The findings indicate that Laura’s blindness intensifies her traumatic perception by forcing her to rely on auditory and tactile impressions, which deepen the fragmentation of her memory.  Her recurring hallucinations of her daughter, emotional volatility, and persistent self-blame align with contemporary trauma studies emphasizing the disrupted relationship between memory, identity, and psychological pain.  The film also suggests the beginning of recovery as Laura gradually confronts avoided memories and regains emotional clarity.  Overall, Bring Her Back presents a multidimensional portrayal of trauma by revealing how unresolved experiences shape one’s memory, identity, and perception of reality.Keywords: identity, memory, psychoanalysis, trauma